STUDI BICULTURAL ETNIS JAWA, TIONGHOA, DAN BATAK PADA PT KARYA TEKHNIK UTAMA DI KOTA BATAM - TENGKU FENNY RIFALNY ALJUFRY; SHOHILUL ABIDIN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Cultural background can affect how people communicate with the others, this also happens in organizational context. Cultural diversity that exists in an organization affects the way of organization members communication. This also happened at PT. Karya Tekhnik Utama which has employess from various cultural backgrounds such as Javanese, Chinese, and Bataknese. The success of an organization is inseparable from the process of communication between individuals who come from different cultural backgrounds in the context of their work. This research emphasizes the study of Javanese, Chinese, and Bataknese ethnic biculturalism at PT. Karya Tekhnik Utama in Batam City. This research uses a qualitative ethnographic approach. Data collection in this study was conducted by interview and observation methods. The results showed that both Javanese, Chinese, and Bataknese when in the context of the work environment tended to try to adjust the norms in the organization such as adapting to the work environment and tended to use ways that were acceptable to the environment in resolving conflicts and expressing opinions